Viability of Cryopreserved Probiotic Strains of Microorganisms Immobilized in Alginate Gel Supplemented with Disaccharides - Petrov, Illia V.; Buriak, Iryna A.; Cherkashina, Yana O. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 171.